ChemInform Abstract: BaFAlSi and BaFAlGe: First Transition Metal‐Free LaOAgS‐Type Fluoride Tetrelides. Issue 13 (March 2015) - Charkin, Dmitri O.; Plokhikh, Igor V.; Kuznetsov, Alexey N.; Kazakov, Sergey M.
Abstract BaFAlSi (I) and BaFAlGe (II) are obtained from attempts to prepare a series of new representatives of Al and Ga tretrelides with the "1111" LaOAgS structure.